2020
DOI: 10.1371/journal.pone.0228919
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes: Effects in phagocytosis and cytokines response against Mycobacterium tuberculosis

Abstract: Cigarette smoking and tuberculosis are a significant cause of death worldwide. Several epidemiological studies have demonstrated cigarette smoking is a risk factor for tuberculosis. Electronic cigarettes have recently appeared as a healthier alternative to conventional smoking, although their impact in tuberculosis is not well understood. The aim of this study was to explore the effect of electronic cigarettes in phagocytosis of Mycobacterium tuberculosis and cytokines production. In vitro infection was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Gilpin [87] and Gomez [88] exposed macrophages and several types of bacteria (e.g., influenza, pneumonia) to e-cigarette aerosol extract and found increased bacterial virulence and inflammatory potential as well as decreased bacteria-killing ability. A mouse study [89] found similar effects for macrophages and increased morbidity and mortality among influenza-infected animals, independent of nicotine.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
See 3 more Smart Citations
“…Gilpin [87] and Gomez [88] exposed macrophages and several types of bacteria (e.g., influenza, pneumonia) to e-cigarette aerosol extract and found increased bacterial virulence and inflammatory potential as well as decreased bacteria-killing ability. A mouse study [89] found similar effects for macrophages and increased morbidity and mortality among influenza-infected animals, independent of nicotine.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
“…Though these studies demonstrated effects of flavorings, some also found significant adverse effects for humectants alone. In several studies [87,88,89,91,92] some effects of e-cigarettes on immune function were less than for cigarettes but some were equal to cigarettes.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation of cytokine production in macrophages by e-cigarette exposure is accompanied by a decrease in their phagocytic activity. Exposure of macrophages to e-cigarette aerosol condensate has been reported to result in a 50-fold increase in ROS production and a significant inhibition of phagocytosis [ 83 ], efferocytosis, and bacterial clearance [ 89 ], and exposing THP-1 macrophages to e-cigarette aerosol extracts has been shown to decrease the intracellular burden of Mycobacterium tuberculosis [ 90 ]. Similarly, when exposed to freshly generated e-cigarette aerosol at the air-liquid interface, alveolar macrophages and neutrophils show reduced anti-microbial activity against Staphylococcus aureus [ 91 ].…”
Section: E-cigarettes and The Immune Responsementioning
confidence: 99%